#1**+1 **

I think this is the equation:

3a^2 + 4a = 2a^2 - 2a - 9

Subtract 2a^2 from both sides of the equation.

a^2 + 4a = - 2a - 9

Add 2a to both sides of the equation.

a^2 + 6a = -9

Add 9 to both sides of the equation.

a^2 + 6a + 9 = 0 \(\leftarrow\) I think this is the standard form of the equaion.

Now we can factor the left side like this

(a + 3)(a + 3) = 0

(a + 3)^2 = 0

Take the square root of both sides.

a + 3 = 0

Subtract 3 from both sides of the equation.

a = -3

hectictar
May 22, 2017